ETHNOPOLITICAL ASPECTS OF NATIONAL SECURITY IN THE GLOBALIZATION ERA - ALLAKHVERDIEV, Kenan (CENTRAL ASIA AND THE CAUCASUS, 2017)
The author has undertaken the challenging task of exploring the complex issues that arise when discussing two highly sensitive social aspects together: a nation's ethnopolitical development and its national security strategy. To address this, the author has examined various approaches to the problem and analyzed the challenges and threats posed by globalization in the ethnopolitical sphere at all levels of security—global, regional, and national. The author has successfully traced the evolution of ideas regarding the ethnopolitical dimension in both political science and practical politics. Initially, the ethnic issue was seen as fully integrated into the social sector of the security system. Over time, this view has evolved to recognize the ethnic dimension of security as a distinct and scientifically substantiated field. Consequently, there is now an acknowledgment of the need for a theoretical and methodological foundation for the ethnopolitical aspect of security, as well as its political-legal institutionalization.